A Decision Support System for sustainable maize harvesting operations scheduling. (23rd February 2007) - Foulds, L.R.; Zhao, Xiao Dan
We describe a Decision Support System (DSS) developed for the scheduling of the operations of contractors who travel from farm to farm to harvest maize. MaizeManager is designed to aid the schedulers of harvesting equipment and personnel in creating or improving schedules, and enables them to use their experience and preferences. A case study is reported, discussing the environment that motivated its development, namely for the harvesting scheduling at Reymers Ltd, New Zealand. The system provides a useful addition to the contracting scheduler's toolkit and an interesting application of the DSS approach to a critical area of agriculture.